Autumn MIST 2019. Issue 4 (1st August 2020) - Walach, Maria-Theresia; Hunt, Greg; Fogg, Alexandra; Bader, Alexander
Abstract : Maria-Theresia Walach, Greg Hunt, Alexandra Fogg and Alexander Bader report on the rescheduled Autumn MIST Meeting for 2019, which took place in January 2020 Abstract: Maria-Theresia Walach, Greg Hunt, Alexandra Fogg and Alexander Bader report on the rescheduled Autumn MIST Meeting for 2019, organized by the MIST Council, which took place in January 2020.